2019
DOI: 10.1017/s002185962000009x
|View full text |Cite
|
Sign up to set email alerts
|

Current status in resistance to ACCase and ALS-inhibiting herbicides in rigid ryegrass populations from cereal crops in North of Tunisia

Abstract: A survey of the prevalence of rigid ryegrass (Lolium rigidum) resistant to ACCase and ALS herbicides was conducted in major-cereal growing regions in the north of Tunisia. Randomly collected ryegrass populations were assessed, using the Syngenta RISQ® test, for resistance to clodinafop-propargyl, iodosulphuron + mesosulphuron and pinoxaden. Of the 177 tested populations, 58% exhibited resistance to clodinafop-propargyl and 52% to iodosulphuron + mesosulphuron, with 40% exhibiting resistance to both herbicides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…According to this study, putative populations resistant to ALS inhibitors could be widely distributed in Northern Tunisia. Similar results were found for D. sophia in China [ 34 ], as well for L. rigidum in Tunisia [ 40 ], another troublesome weed species in the region, which behaved similarly and had evolved resistance in 87% of tested populations [ 41 ]. At field rate, at least for one of the two sulfonylureas tested, the dry weight increased compared to nontreated plants in most populations which suggest a hormetic effect induced in G. coronaria resistant plants.…”
Section: Discussionsupporting
confidence: 75%
“…According to this study, putative populations resistant to ALS inhibitors could be widely distributed in Northern Tunisia. Similar results were found for D. sophia in China [ 34 ], as well for L. rigidum in Tunisia [ 40 ], another troublesome weed species in the region, which behaved similarly and had evolved resistance in 87% of tested populations [ 41 ]. At field rate, at least for one of the two sulfonylureas tested, the dry weight increased compared to nontreated plants in most populations which suggest a hormetic effect induced in G. coronaria resistant plants.…”
Section: Discussionsupporting
confidence: 75%
“…Results from this study revealed the development of cross-resistance to ALS-inhibiting herbicides in two G. coronaria populations from the Bizerte region in northern Tunisia. Since their introduction in 1999, the SU herbicides were excessively used by the Tunisian wheat growers to control troublesome grass weeds such as L. rigidum ( Khammassi et al, 2020 ) and dicotyledonous weeds. The main reason was their broad-spectrum weed control at low rates.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there have been numerous herbicide resistance surveys of specific cropping regions 28–33 that typically focus on single weed species at one point in time, screened with herbicides representing a limited selection of modes of action (MOAs). These surveys provide a ‘snapshot in time’ description of the extent of herbicide resistance, however, they have not typically been repeated and any subsequent changes in resistance types or distribution have not been tracked.…”
Section: Herbicide Resistance Surveysmentioning
confidence: 99%